PRAKTIK TERBAIK KEPEMIMPINAN PENDIDIKAN DALAM MEMBIMBING MAHASISWA UNIVERSITAS MERANGIN DI SDU MUHAMMADIYAH MERANGIN - Yesi Elfisa; M. Ali Basroh; Shobrina Fitri; Cusan Hewa; Aina Desria Fitri (Hira Institute, 2025)
Educational leadership is an important aspect of the academic world, particularly for pre-service teacher students who are undergoing teaching practice in schools. This activity aims to identify and analyze the best practices of educational leadership demonstrated by students of Merangin University during their teaching practice at SDU Muhammadiyah Merangin. Leadership refers to an individual's ability to direct, influence, and motivate others, serving as a foundation for the development of personal character. The implementation method of this community service activity consists of three main stages: observation, interviews, and formulation of recommendations. The primary goal of this activity is to develop effective and inspiring leadership skills among student teachers. In addition, the program also aims to foster a positive school environment, as reflected in the leadership practices at SDU Muhammadiyah Merangin in cultivating religious values and understanding of social sciences in students' daily lives.